THE EXISTENCE OF CAREER WOMEN IN INSTALLING RELIGIOUS AND MORAL VALUES IN EARLY CHILDREN IN THE COLLEGE ENVIRONMENT OF THE ISLAMIC RELIGIOUS INSTITUTE AL-QODIRI JEMBER - Fitriya, Anita; Abdillah, Fajar (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
For a mother who is involved in the career world, it is certainly not easy to share roles professionally. Mothers are the first to educate and introduce children to the world. In educating a child, the most important thing to instill is religious and moral values ​​because religion and morals are the main foundation in forming a human character. That is why it is so important to instill aspects of religious and moral values ​​in children as early as possible. This research aims to describe the strategies used by career women in instilling religious and moral values ​​in early childhood and the obstacles faced by career women in the Al-Qodiri Jember Islamic Institute Higher Education. This research approach uses qualitative, the type of design used is a case study. The technique for determining informants uses purposive sampling and snowball. while data collection techniques use observation, interviews and documentation. The researcher's data analysis technique refers to the Miles and Huberman model, namely: data reduction, data presentation and drawing conclusions. Data validity uses source triangulation and technique triangulation. The research results show that the strategy used by career women in instilling religious and moral values ​​is through Direct strategies include increasing prayer while the child is still in the womb, being exemplary in congregational prayers, reciting the Koran together, fasting, memorizing prayers or short letters every night and getting into the habit of saying thank you, using the word please, saying hello, respecting elders and kissing. the hands of an older person. An indirect strategy is to send children to religious schools in the morning and entrust their children to TPQ in the afternoon. Barriers to career women in instilling moral and religious values ​​in early childhood are external, originating from outside the child in the form of limited parental time, inability to control influences. bad friends and the bad influence of social media.